If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -1)(9x + 3) = 0 Reorder the terms: (-1 + 5x)(9x + 3) = 0 Reorder the terms: (-1 + 5x)(3 + 9x) = 0 Multiply (-1 + 5x) * (3 + 9x) (-1(3 + 9x) + 5x * (3 + 9x)) = 0 ((3 * -1 + 9x * -1) + 5x * (3 + 9x)) = 0 ((-3 + -9x) + 5x * (3 + 9x)) = 0 (-3 + -9x + (3 * 5x + 9x * 5x)) = 0 (-3 + -9x + (15x + 45x2)) = 0 Combine like terms: -9x + 15x = 6x (-3 + 6x + 45x2) = 0 Solving -3 + 6x + 45x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-1 + 2x + 15x2) = 0 Factor a trinomial. 3((-1 + -3x)(1 + -5x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -3x)' equal to zero and attempt to solve: Simplifying -1 + -3x = 0 Solving -1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 0 + 1 -3x = 0 + 1 Combine like terms: 0 + 1 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333Subproblem 2
Set the factor '(1 + -5x)' equal to zero and attempt to solve: Simplifying 1 + -5x = 0 Solving 1 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5x = 0 + -1 -5x = 0 + -1 Combine like terms: 0 + -1 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2Solution
x = {-0.3333333333, 0.2}
| 6x+11=-7 | | 35mi=cm | | 4w+7y+7x+4x-14y+4w= | | 36y^2+12y+1-x^2= | | 3x+-11=10 | | 2x+119=95 | | 13f+41=-20+5f | | 2f+5f=27 | | 4w+8x+12y+4w+3x-5y= | | 7x-6+x=8x | | 11n=7n+12 | | x^2+y^2+36=0 | | 3(x+3)=69 | | 4+3p=21 | | (A+2)x-b=ax+c | | 2x^2+4x=x^2+x+1 | | 2(10n-7)=18-12n | | 2x+7x-(6x+7)= | | 5x-3=x+25 | | 3x+3=47-8x | | 4x+2(x-5)=38 | | 18=-3x+2(-x-1) | | 2(x-8)=6 | | 5(3+2x)=7+5x | | 3x+4x+3x=10x | | 11-4(3x+4)=5(7-5x) | | 8x+2+5x+9=12x-4 | | Sin(x)=0.43 | | 3x+1000000000x=32 | | t^2-8t-2=0 | | 9x=49+2x | | -3x+(-8)x+14=26+13 |